Validação de metodologia analítica por CLAE-DAD para determinação de compostos fenólicos e atividade biológica em coprodutos agroindustriais - Silva, Rafaéla Candido Oliveira da (2016)
The southern region of Brazil, especially the states of Parana and Santa Catarina stand out for growing grapes and apples for fresh consumption and in order to add value to these products, process the material for the production of wine, juices and jellies . As a result large quantities of by-products, such as peels, seeds and pulp are produced becoming environmental problems. Studies reuse of these by-products have attracted interest because they have shown a high biological potential, due to the presence of high levels of phenolic compounds, which are associated with a lower incidence of disease caused by oxidative stress, due to its antioxidant, antiinflammatory and antibacterial properties. Currently, few studies are presented on the phenolic composition and biological potential of waste grape variety Bordô (Vitis labrusca) and apple (Malus domestica) Gala variety, cultivated in southern Brazil. Within this context, the objectives of this study were: compare the efficiency of solidliquid and liquid-liquid extraction, perform the optimization and validation of analytical methodology by HPLC-DAD for the separation, identification and quantification of multiclass phenolic compounds, evaluate the activity antioxidant by sequestering methods of free radical 2,2-diphenyl-1 picrilhidrazina (DPPH) and 2,2-azino-bis (3- ethyl-benzthiazoline-6-sulphonic acid) (ABTS) solution, reduction of Fe3+ in Fe2+ method (FRAP), ORAC, RP-HPLC-ABTS online, Rancimat and determination of total phenolics three agro-industrial byproducts, pomace and stems grape Bordô produced in Paraná Southwest region and Gala apple pomace coming from the Santa Catarina West. Optimization and validation of chromatographic method showed satisfactory quality parameters for the compounds of interest and the solidliquid extraction was more efficient in extracting phenolic evaluated. The three byproducts evaluated showed significant levels of phenolic compounds when analyzed by HPLC, especially flavonoids, catechin and epicatechin besides that showed significant antioxidant capacity. The grape stems extract had the highest sequestration capacity of DPPH and ABTS radical and reduced iron, and high content of phenolic compounds. The apple pomace extract showed the best response to the Rancimat method, which indicates a high potential to protect the oil from lipid oxidation, was no significant difference when compared to synthetic antioxidant TBHQ. The results of this study showed that the agro-industrial coproducts analyzed are rich in phenolic compounds of high antioxidant capacity and therefore must be better explored by the food and pharmaceutical industries.